What limits evaporation from Mediterranean oak woodlands – The supply of moisture in the soil, physiological control by plants or the demand by the atmosphere? - Baldocchi, Dennis D.; Xu, Liukang (Advances in Water Resources, 2007)
The prediction of evaporation from Mediterranean woodland ecosystems is complicated by an array of climate, soil and plant factors. To provide a mechanistic and process-oriented understanding, we evaluate theoretical and experimental information on water loss of Mediterranean oaks at three scales, the leaf, tree and woodland. We use this knowledge to address: what limits evaporation from Mediterranean oak woodlands – the supply of moisture in the soil, physiological control by plants or the demand by the atmosphere? The Mediterranean climate is highly seasonal with wet winters and hot, dry summers. Consequently, available sunlight is in surplus, causing potential evaporation to far exceed available rainfall on an annual basis. Because the amount of precipitation to support woody plants is marginal, Mediterranean oaks must meet their limited water supply by a variety of means. They do so by: (1) constraining the leaf area index of the landscape by establishing a canopy with widely spaced trees; (2) reducing the size of individual leaves; (3) by adopting physiological characteristics that meter the use of water (e.g. regulating stomatal, leaf nitrogen/photosynthetic capacity and/or hydraulic conductance); (4), by tapping deep supplies of water in the soil; (5) and/or by adopting a deciduous life form, which reduces the time interval that the vegetation transpires.
Keywords: ecohydrology; evaporation; quercus douglasii; savanna; Transpiration